Non-Clinical Benefits of Evidence-Based Veterinary Medicine - Jackson, Elizabeth; Hauser, S. (2016)
There are few studies addressing business benefits of evidence-based veterinary medicine (EBVM). While the need for a wider adoption of EBVM has been highlighted and linked to commercial benefits, further empirical studies are needed to identify and quantify such link.